Symptomatology of Musculoskeletal Pain Related to Repetitive Movements. Preliminary Study “Post-harvest in Floriculture Companies” - Morales, Luis (2020)
Musculoskeletal injuries affect the health of workers worldwide. This research relates the repetitive movements with the generation of musculoskeletal injuries in workers of the post-harvest area of a flower company. The evaluation methodology is the OCRA check list. The symptomatology of musculoskeletal pain was evaluated applying the Nordic questionnaire. The injuries were determined comparing morbidity rates and medical records of a sample of eighteen workers in Flores del Cotopaxi S.A. The results show that there is risk due to repetitive movements in activities like classification and bunching. Statistical tests established significant incidence (p = 0.015) for chi-square and (OR = 15), Odds Ratio. In both tests a confidence level of 95% was used. In the post-harvest area exist risks as a consequence of repetitive movements linked to the generation of musculoskeletal injury, mainly in the shoulders and wrists. © Springer Nature Switzerland AG 2020.